Pembrolizumab activity in patients with Fanconi anemia repair pathway competent and deficient tumors - Miguel A. Villalona-Calero; John P. Diaz; Wenrui Duan; Zuanel Diaz; Eric D. Schroeder; Santiago Aparo; Troy Gatcliffe; Federico Albrecht; Siddhartha Venkatappa; Victor Guardiola; Sara Garrido; Muni Rubens; et al. (BMC, 2022)
Abstract Background Given the observed antitumor activity of immune-checkpoint-inhibitors in patients with mismatch-repair deficient (MSI-H) tumors, we hypothesized that deficiency in homologous-recombination-repair (HRR) can also influence susceptibility. Methods Patients with disease progression on standard of care and for whom pembrolizumab had no FDA approved indication received pembrolizumab. Patients with MSI-H tumors were excluded. Objectives included immune-related objective response rate (iORR), progression-free survival (PFS) and 20-weeks-PFS. Pembrolizumab was given every 3 weeks and scans performed every six. We evaluated a triple-stain (FANCD2foci/DAPI/Ki67) functional assay of the Fanconi Anemia (FA) pathway: FATSI, in treated patients' archived tumors. The two-stage sample size of 20/39 patients evaluated an expected iORR≥20% in the whole population vs. the null hypothesis of an iORR≤5%, based on an assumed iORR≥40% in patients with functional FA deficiency, and < 10% in patients with intact HRR. An expansion cohort of MSI stable endometrial cancer (MS-EC) followed. Exploratory stool microbiome analyses in selected patients were performed. Results Fifty-two patients (45F,7M;50-evaluable) were enrolled. For the 39 in the two-stage cohort, response evaluation showed 2CR,5PR,11SD,21PD (iORR-18%). FATSI tumor analyses showed 29 competent (+) and 10 deficient (−). 2PR,9SD,17PD,1NE occurred among the FATSI+ (iORR-7%) and 2CR,3PR,2SD,3PD among the FATSI(−) patients (iORR-50%). mPFS and 20w-PFS were 43 days and 21% in FATSI+, versus 202 days and 70% in FATSI(−) patients. One PR occurred in the MS-EC expansion cohort. Conclusions Pembrolizumab has meaningful antitumor activity in malignancies with no current FDA approved indications and FA functional deficiency. The results support further evaluation of FATSI as a discriminatory biomarker for population-selected studies.